Clinicopathological and prognostic significance of PD‐1/PD‐L1 axis expression in patients with tongue squamous cell carcinoma. Issue 10 (6th February 2020) - Huang, Weilun; Zhou, Xiao; Liao, Qianjin; Tang, Yanyan; Zuo, Liang; Wang, Honghan; Chen, Xing; Chen, Xiaoyan; Li, Junjun; Zhu, Songlin; Deng, Jun; Liu, Yan; et al.
Abstract: Tongue squamous cell carcinoma (TSCC) is more aggressive than other head and neck tumors, and the prognosis for patients with advanced TSCC is poor. At present, comprehensive treatment based on surgery as the main method is not effective for patients with advanced TSCC. The application of PD‐1/PD‐L1 immunocheckpoint inhibitor alone in patients with TSCC has not been reported. To explore the role of PD‐1/PD‐L1, we investigated the expression of PD‐1 and PD‐L1 in TSCC and analyzed the relationship between the expression of PD‐1 and PD‐L1 and the related clinicopathological parameters and survival prognosis. The expression of PD‐1 was significantly associated with palindromia ( p = .015) and maximum diameter ( p = .043). The expression of PD‐L1 in tumor cells was significantly associated with N stage ( P = .024), chemotherapy ( p = .032), and clinical stage ( p = .019). The expression of PD‐L1 in infiltrating lymphocytes was significantly associated with palindromia ( p = .030). Univariate and multivariate Cox analyses for prognoses of patients showed significant prognostic factors of overall survival and relapse‐free survival. The high expression of PD‐L1 on infiltrating lymphocytes for OS and RFS was an independent protective factor for patients with TSCC. The high expression of PD‐1 on infiltrating lymphocytes and clinical stage for OS and RFS were independent risk factors for patients with TSCC. The data provide a reference for clinical treatment of TSCC with immunotherapy.